Instrumentación de la Norma Técnica de Calidad NTC-GP 1000 en la Corporación Concejo Municipal de Armenia (2015)
The Municipal Council of Armenia Corporation considered essential to establish a system of quality management, not only in order to comply with current regulations but also in order to seek continuous improvement in the development of its functions, ensuring a high level of quality and optimal service to the community in Armenia. In this sense, the Municipal Council of Armenia has been proposed to achieve certification in the implementation of the Technical Quality Standard for Public Management, NTC-GP 1000, with the aim of improving quality in the provision of their services, satisfying the community needs and strengthening its image as a public entity. According to the above, the internship consists in developing the documentation process of System Quality Management in accordance with the requirements and provisions of the Technical Regulations mentioned, starting with a diagnosis of the current situation of the corporation in relation to the standard, to end with the implementation of different formats, procedures and other documentation created, allowing demostrate a sufficient degree of compliance for subsequent certification by the entity.